Ethyl acetate extract of Elephantopus mollis Kunth induces apoptosis in human gastric cancer cells - Tran Dang Thanh Tam; Truong Thi Bich Ngoc; Nguyen Thi Hoai Nga; Nguyen Thi My Trinh; Tran Linh Thuoc; Dang Thi Phuong Thao (BMC, 2021)
Abstract Background Gastric cancer is one of the most leading causes of cancer death worldwide. Therefore, treatment studies have been being conducted, one of which is screening of novel agents from medicinal herbs. Elephantopus mollis Kunth (EM) belonging to Asteraceae family is a perennial herb with several therapeutic properties including anticancer activity. However, the effect of this species on gastric cancer has not been reported yet. In this study, cytotoxicity of different EM crude extracts was investigated on AGS gastric cancer cell line. Besides, the effects of extract on nuclear morphology, caspase-3 activation, and gene expression were also explored. Results The results showed that ethyl acetate extract exhibited a remarkably inhibitory ability (IC50 = 27.5 μg/ml) on the growth of AGS cells, while causing less toxicity to normal human fibroblasts. The extract also induced apoptotic deaths in AGS cells as evidenced by cell shrinkage, formation of apoptotic bodies, nuclear fragmentation, caspase-3 activation, and the upregulation of BAK and APAF-1 pro-apoptotic genes related to mitochondrial signaling pathway. Specifically, BAK and APAF-1 mRNA expression levels showed 2.57 and 2.71-fold increases respectively. Conclusions The current study not only proved the anti-gastric cancer activity of EM ethyl acetate extract but also proposed its molecular mechanism. The extract could be a potential candidate for further investigation.